Private motorized transport, Los Angeles, USA - Anderton, K (Routledge, 2014)
Los Angeles (LA) became a city synonymous with the automobile during the course of the twentieth century. Nowhere conjures images of endless concrete corridors more so than the ‘city of Angels’. Banham spoke of LA’s freeway system as a ‘single comprehensible place, a coherent state of mind, a complete way of life’ (1971). This case study examines the city’s affinity with the car, how it came about, and the issues that the city faces as a consequence of its congested, auto-dominated infrastructure and development choices of the past. The key issues examined are sprawl and the unabated land take for roads in the city, smog and air pollution and the associated health effects that they create, and access to mobility.